Principles of administrative legal proceedings in modern conditions: scientific and legal aspect - M. V. Dzhafarova (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to a scientific and theoretical study of the principles of administrative legal proceedings in the updated conditions of the Ukrainian State development, based on the needs for high-quality provision and implementation of legal rights, freedoms and interests of individuals and legal entities in the field of public law relations. It has been established that the principles of administrative proceedings at the current stage of development of administrative procedural law should be understood as the basic, initial rules which are stipulated by the provisions of national legislation, as well as generally accepted provisions of international law and standards of administration of justice, and which determine the organisational and functional (procedural) conditions for the administration of justice in administrative cases, and which are reflected and enshrined in the relevant provisions of the Code of Administrative Procedure of Ukraine. It has been noted that by their functional purpose, the principles of administrative justice form a stable basis for the functioning of the mechanism of administrative and procedural regulation.